Various approaches to daily milk yield prediction from alternative milk recording scheme - Gantner, Vesna; Jovanovac, Sonja; Kovač, Miena; Malovrh, Špela; Kompan, Drago (Acta Agraria Kaposváriensis, 2006)
The objective of this research was to compare different approaches to daily milk yield prediction from alternative milk recording scheme (single morning and evening milking records). The data used in this study were 3.730 individual test-day milk yield records collected from November 2004 to November 2005 on 560 cows reared on 15 family farms in Croatia. Daily milk yield, as well as, daily fat and protein content were predicted by several different approaches. The correlations between true and estimated daily milk yield are slightly lower when prediction is based on evening milkings, while the correlations between true and estimated daily fat as well as protein content are slightly higher when prediction is based on evening milkings. Model D, which included single yields as covariate as well as effect of daily interval, and model E, which also included effect of lactation stage as lactation curve by Ali and Schaeffer, gives the best fit to the data both for prediction of daily milk yield or milk content (fat and protein) based on morning or evening milkings. Differences between those two models were minor and statistically insignificant, so we would recommend use of model D in practice as the model which could be easier to implement in routine work.